PENGARUH DIGITAL WORK ENVIRONMENT DAN PSYCHOLOGICAL EMPOWERMENT TERHADAP WORK ENGAGEMENT DENGAN KESEJAHTERAAN KARYAWAN SEBAGAI VARIABEL MEDIASI: STUDI KASUS RSD BALUNG JEMBER - Tristati, Imelda Inka; widodo, Agus purbo; Sudarsono, Heri (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2025)
The digital transformation in the workplace requires organizations, including hospitals, to establish adaptive, innovative, and empowering work environments. A digital-based work environment is considered an essential factor that can enhance employee engagement, particularly when supported by psychological empowerment and adequate employee well-being. This study aims to analyze the influence of the Digital Work Environment (DWE) and Psychological Empowerment (PE) on Work Engagement (WE), with Employee Well-Being (EW) as a mediating variable. The research was conducted at Balung District Hospital, Jember, involving 126 respondents selected using a proportional random sampling technique to ensure representation across both medical and non-medical staff categories. Data were collected through a structured questionnaire measured on a five-point Likert scale, which was tested for validity and reliability. The data were analyzed using Structural Equation Modeling (SEM) with the AMOS software. These results highlight the strategic role of digital infrastructure, psychological empowerment, and employee well-being in fostering higher levels of work engagement. This study is expected to contribute theoretically to the field of human resource management research and provide practical implications for hospital management in optimizing employee performance. Keywords: Digital Work Environment, Psychological Empowerment, Employee Well-Being, Work Engagement